Factors Affecting The Rupiah Exchange Rate Over The United States Dollar in Indonesia - Irwandi; Regina; Rahmizal, Maizul (Economics and Business Journal (ECBIS), 2023)
This study examines the factors that affect the exchange rate of the rupiah against the US dollar in Indonesia between 2013-2022. The observed factors include interest rates, inflation, and money supply. Annual data was used from legitimate sources such as Bank Indonesia and the Central Bureau of Statistics. The results show that interest rates have a significant influence on the rupiah exchange rate, with an increase in interest rates causing a depreciation of the rupiah against the US dollar. Inflation has no significant effect on the exchange rate, although high inflation can affect purchasing power and confidence in the local currency. Money supply also has a significant effect, where an increase tends to cause rupiah depreciation. An increase in money supply causes inflation and decreases purchasing power, thus decreasing the exchange rate of the rupiah against the US dollar